2009
DOI: 10.1007/s10457-009-9254-6
|View full text |Cite
|
Sign up to set email alerts
|

Temporal changes in VAM fungi in the cocoa agroforestry systems of central Cameroon

Abstract: In Cameroon, cocoa trees are mostly grown in forests and without fertilization. Our aim was to learn more about the temporal dynamics of soils in cocoa agroforests by comparing young (1-4 years old) and old (over 25 years old) cocoa agroforests. Short fallow and secondary forest were used as treeless and forest references. The numbers and diversities of soil vesicular arbuscular mycorrhizal (VAM) fungi on 60 cocoa producing farms in the Central province of Cameroon were assessed based on the classical morphoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…This is not surprising since it was previously shown that Glomus and acaulospora species are most abundant among the glomeromycotan genera in tropical areas (Gerdemann and Trappe, 1974;Blaszkowski, 1989;Talukdar and Germida, 1993;Zerihun Belay et al, 2014). Glomus species is widely distributed regardless of the type and intensity of disturbance in the different ecosystems, whereas Acaulospora is dominant in least disturbed agro ecosystems (Snoeck et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This is not surprising since it was previously shown that Glomus and acaulospora species are most abundant among the glomeromycotan genera in tropical areas (Gerdemann and Trappe, 1974;Blaszkowski, 1989;Talukdar and Germida, 1993;Zerihun Belay et al, 2014). Glomus species is widely distributed regardless of the type and intensity of disturbance in the different ecosystems, whereas Acaulospora is dominant in least disturbed agro ecosystems (Snoeck et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Lower AMF species richness has been found in arable fields, while species-rich AMF communities were detected in different natural ecosystems and perennial communities such as tropical forest (Snoeck et al, 2010). Studies from the tropics indicate that the AMF species richness in a monoculture like sugarcane grown in fertile soils (Colombian Mollisols) can be high (Sieverding, 1991).…”
Section: Arbuscular Mycorrhizal Fungal Diversitymentioning
confidence: 99%
“…Once established, cacao remains in the same field for decades, therefore cocoa fields are dominated with aging trees growing on variable and depleted soils (Snoeck et al, 2010). In Trinidad and Tobago like many cocoa producing countries, increase in cocoa production is mainly due to expansion of existing farms or creation of new farms rather than increase in yield per unit area (Gockowski, 2007;Snoeck et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Once established, cacao remains in the same field for decades, therefore cocoa fields are dominated with aging trees growing on variable and depleted soils (Snoeck et al, 2010). In Trinidad and Tobago like many cocoa producing countries, increase in cocoa production is mainly due to expansion of existing farms or creation of new farms rather than increase in yield per unit area (Gockowski, 2007;Snoeck et al, 2010). While technological approaches to address within-field variability have resulted in stupendous increase in yield per unit area in the production of other crops, cocoa production still relies on inefficient and outdated traditional production and management methods that do not take into account withinfield soil variability.…”
Section: Introductionmentioning
confidence: 99%